The Phenomenon of Polyphony in the Short Story Collection “The Seagull Man” by the Libyan Writer Hussein Nassib Al-Maliki - Haruna, Haruna Abubakar; Asmai, Ali Mahmood (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2022)
This study aims to illuminate the features of the relationship of the narrator character in the story group, with the narrative that contributes to its presentation through the story, and the impact of that relationship on the narrative consistency in it. The Libyan